Cervical and Lower Uterine Parameter Ultrasound and Elastographic Parameters for the Prediction of a Successful Induction of Labor - Hamza, Amr; Radosa, Julia; Gerlinger, Christoph; Solomayer, Erich Franz; Ströder, Russalina; Meyberg-Solomayer, Gabriele (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose The prediction of successful induction of labor (IOL) has been the subject of a series of studies. The predictive role of cervical sonographic and elastographic parameters has been controversially discussed. Lower uterine segment (LUS) thickness and strain values have not been discussed yet in this regard.Materials and Methods A prospective cohort study was performed to examine the predictive power of Bishop score parameters, sonographic cervical length (CL), cervical funneling, cervical strain values, LUS thickness and its strain values regarding successful IOL within 24 hours and intervals to onset of labor, ROM and delivery of the fetus. A p-value of < 0.05 was considered statistically significant.Results 135 patients were examined. A cervical length of 25 mm, the presence of cervical funneling and digital shorter cervix was significant for the prediction of successful induction of labor (IOL) within 24 hours. There was weak correlation between the functional CL and the onset of labor (r2 = 0.10) and ROM (r2 = 0.13). There was also a weak correlation between the cervical funnel width and the time interval to the onset of labor (r2 = 0.25), ROM (r2 = 0.23) and delivery of the fetus (r2 = 0.22). Cervical elastography, LUS thickness and strain values were not significant for the prediction of a successful IOL.Conclusion We were able to show that cervical structural changes at the level of the internal os, i. e., shortening through funneling, may be the determining factor for successful IOL.
Keywords: elastography; lower uterine segment; induction of labor; ultrasound